2020
DOI: 10.1007/s00192-020-04250-3
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum sexual function; the importance of the levator ani muscle

Abstract: Introduction and hypothesis Pelvic floor muscle function plays an important role in female sexual functioning. Smaller genital hiatal dimensions have been associated with sexual dysfunction, mainly dyspareunia. On the other hand, trauma of the levator ani muscle sustained during childbirth is associated with increased genital hiatus, which potentially can affect sexual functioning by causing vaginal laxity. This study aims to determine the association between levator hiatal dimensions and female sexual dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Trauma to the levator ani during vaginal childbirth is associated with female pelvic organ prolapse 31 and has been suggested but not confirmed to have an association with symptoms of urinary and anal incontinence 32 , 33 . Regarding sexual function, a recent study found no association between postpartum levator hiatus and sexual dysfunction 34 .…”
Section: Discussionmentioning
confidence: 93%
“…Trauma to the levator ani during vaginal childbirth is associated with female pelvic organ prolapse 31 and has been suggested but not confirmed to have an association with symptoms of urinary and anal incontinence 32 , 33 . Regarding sexual function, a recent study found no association between postpartum levator hiatus and sexual dysfunction 34 .…”
Section: Discussionmentioning
confidence: 93%
“…The study found that 13.00 %–14.00 % of primipara have postpartum levator ani muscle injury during delivery [ 23 ]. It is reported that the probability of levator ani injury after vaginal delivery of primipara in China is as high as 21.70 % [ 24 ]. Postpartum levator ani injury not only increases the pain of the parturient, but also affects the rapid recovery of the parturient.…”
Section: Discussionmentioning
confidence: 99%
“…Narrowing of this APDH has been related to hypertonia [ 9 , 11 , 12 , 13 ]. USI measures of the APDH have been used to evaluate pelvic floor function in different statuses (rest, active contraction and Valsalva) and to assess pre-post treatment changes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted in gynecological cancer survivors and patients with endometriosis showed differences in pelvic floor architecture related with DP [ 9 , 24 , 25 , 26 ]. APH and hiatus area have been explored in several studies in women after childbirth, concluding that no direct or isolated relation with DP could be found [ 14 , 27 ]. To the authors’ knowledge, abdominal wall features of this group have not been assessed up to this date.…”
Section: Introductionmentioning
confidence: 99%